2015
DOI: 10.1016/j.neurobiolaging.2015.02.018
|View full text |Cite
|
Sign up to set email alerts
|

The loss of glucose-regulated protein 78 (GRP78) during normal aging or from siRNA knockdown augments human alpha-synuclein (α-syn) toxicity to rat nigral neurons

Abstract: Age-related structural changes and gradual loss of key enzymes significantly affect the ability of the Endoplasmic Reticulum (ER) to facilitate proper protein folding and maintain homeostasis. In this work we present several lines of evidence supporting the hypothesis that the age-related decline in expression of the ER chaperone glucose regulated protein GRP78 (GRP78) could be related to the development of Parkinson’s disease (PD). We first determined that old (24 month) rats exhibit significantly lower level… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
55
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(60 citation statements)
references
References 37 publications
5
55
0
Order By: Relevance
“…Old mice (20–24 months old) have 20% less GRP78 ATPase activity than young mice (3–5 months old), which is consistent with a 2-fold higher level of GRP78 carbonylation in old mice. Such findings support the hypothesis that loss of ER or other cellular functions, often seen in age-related diseases, is caused by the life-long accumulation of oxidative damage to key proteins (Nuss et al, 2008; Salganik et al, 2015). Another study reported that there was about 73% less GRP78 mRNA in old (900 days old) compared to young (21 days old) rats, suggesting that loss of GRP78 activity and the associated physiological declines occur at both the protein and transcript levels (Erickson et al, 2006).…”
Section: Grp78 In Neurodegenerative Processessupporting
confidence: 77%
“…Old mice (20–24 months old) have 20% less GRP78 ATPase activity than young mice (3–5 months old), which is consistent with a 2-fold higher level of GRP78 carbonylation in old mice. Such findings support the hypothesis that loss of ER or other cellular functions, often seen in age-related diseases, is caused by the life-long accumulation of oxidative damage to key proteins (Nuss et al, 2008; Salganik et al, 2015). Another study reported that there was about 73% less GRP78 mRNA in old (900 days old) compared to young (21 days old) rats, suggesting that loss of GRP78 activity and the associated physiological declines occur at both the protein and transcript levels (Erickson et al, 2006).…”
Section: Grp78 In Neurodegenerative Processessupporting
confidence: 77%
“…Gorbatyuk et al (9) reported that overexpression of GRP78 diminished ␣-synuclein neurotoxicity in a rat model of PD by downregulating ER stress. More recently, Salganik et al (40) found that GRP78 protein overexpression protected aging nigral dopamine neurons in the ␣-synuclein-induced rat model of PD. Rotenone has been reported to induce ER stress both in cell models and animal models of PD (10,11,49).…”
Section: Discussionmentioning
confidence: 99%
“…Mounting evidence has shown that with advancing age, ER-related stress gradually elevates in brain (Chen et al, 2013; Naidoo et al, 2011). Moreover, it was recently shown that the ER chaperones, such as glucose-regulated protein 78 (GRP78), decline significantly with aging (Naidoo et al, 2008; Salganik et al, 2015). The decline of GRP78 could be potentially related to the development of Parkinson’s disease.…”
Section: Impact Of Aging On the Components Of The Nvumentioning
confidence: 99%
“…The decline of GRP78 could be potentially related to the development of Parkinson’s disease. Moreover, the degree of chaperone decline corresponds with the severity of neurodegeneration (Salganik et al, 2015). …”
Section: Impact Of Aging On the Components Of The Nvumentioning
confidence: 99%